1972
DOI: 10.1080/09553007214551021
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Division Delay inDictyostelium Discoideum:Relation to Survival in Resistant and Sensitive Strains

Abstract: Vegetative amoeboid cells of the cellular slime mould, Dictyostelium discoideum NC-4, are very resistant to gamma-radiation . Mutant strains have been isolated which are significantly more radiosensitive . Studies were conducted to measure division delays and other growth responses after irradiation of strain NC-4 and two mutant strains . Some division of non-surviving (non-colonyforming) cells was observed in all strains . Total cell populations (surviving plus non-surviving cells) in all three strains showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Support for the idea that longer delay may, in·general, result in more repair and, therefore, greater survival, apparently was obtained from experiments with vegetative amoeboid cells of Dictyostelium discoideum (Cleveland and Deering 1972). Cleveland and Deering found that the survivors of irradiated cells of radiosensitive strains suffered unusually long division delays compared to the total cells in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the idea that longer delay may, in·general, result in more repair and, therefore, greater survival, apparently was obtained from experiments with vegetative amoeboid cells of Dictyostelium discoideum (Cleveland and Deering 1972). Cleveland and Deering found that the survivors of irradiated cells of radiosensitive strains suffered unusually long division delays compared to the total cells in the population.…”
Section: Discussionmentioning
confidence: 99%